Use of the National Heart, Lung, and Blood Institute Data Repository - Coady, Sean A. (N Engl J Med, 2017)
BACKGROUND: Research on data sharing from clinical trials has focused on elucidating perceptions, barriers, and attitudes among trialists and study participants with respect to sharing data. However, little information exists regarding utilization or associated publication of articles once clinical trial data have been widely shared. METHODS: We analyzed administrative records of investigator requests for data access, linked publications, and bibliometrics to describe the use of the National Heart, Lung, and Blood Institute data repository. RESULTS: From January 2000 through May 2016, a total of 370 investigators requested data from 1 or more clinical trials. Requests for trial data have been increasing, with 195 investigators (53%) initiating requests during the last 4.4 years of the study period. The predominant reason for requesting data was post hoc secondary analysis of new questions (72%), followed by analytic or statistical approaches to clinical trials (9%) and meta-analyses or pooled study research (7%). Of 172 requests with online project descriptions, only 2 requests were initiated for reanalysis of primary-outcome findings. Data from 88 of 100 available clinical trials were requested at least once, and the median time from repository availability to first request was 235 days. A total of 277 articles were published on the basis of data from 47 trials. Citation metrics from 224 articles indicated that half of the publications have cumulative citations that rank in the top 34% normalized for subject category and year of publication. CONCLUSIONS: Demand for trial data for secondary analysis has been increasing. Requesting data for the a priori purpose of reanalysis or verification of original findings was rare.